Tissue reactions to polyethylene glycol and glutaraldehyde-based surgical sealants in a rabbit aorta model. (April 2020) - Slezak, Paul; Klang, Andrea; Ferguson, James; Monforte, Xavier; Schmidt, Peter; Bauder, Barbara; Url, Angelika; Osuchowski, Marcin; Redl, Heinz; Spazierer, Daniel; Gulle, Heinz
Surgical sealants help achieve rapid haemostasis when applied as an adjunct to sutures in vascular surgery, but their use can lead to various side effects. This study compared the local inflammatory reaction to commercially available BioGlue and Coseal sealants in a rabbit aorta suture hole model. Twenty male New Zealand white rabbits were randomised to testing with either BioGlue or Coseal. Two weeks after sealant application to suture holes, sections of the aorta at the puncture site, and surrounding tissue, were processed for histopathological analysis. Inflammation was graded from 0 to 3 according to tissue alteration and presence of inflammatory cells. Material stiffness was measured in vitro using compression testing. From examination of the inflammatory response to the sealants, a less severe histopathological assessment score was assigned to the Coseal compared to the BioGlue group (mean ± SD: 1.56 ± 0.53 vs 2.67 ± 0.50; p = 0.002). While both materials triggered a typical foreign body reaction characterised by granulomatous inflammation, BioGlue additionally provoked eosinophilic cell infiltration. Lymphocytes, plasma cells and B cells were also more prevalent in the BioGlue compared to the Coseal specimens. Coseal residue was either absent or visible in only small quantities, while significant BioGlue deposits remained in the tissue 2 weeks after application. Coseal was much more elastic than BioGlue, with a compressive modulus an order of magnitude lower (mean ± SD: 91 ± 41 vs 1833 ± 297 kPa). Compared to BioGlue, Coseal elicited a less pronounced inflammatory response in the aortic and peri-aortic tissue in this model, and demonstrated greater elasticity.